An Unusual Case of Asystole following Penetrating Neck Trauma and Anoxic Brain Injury - Matthew Nayor; Alissa J. Berliner; Grant V. Chow; David D. Spragg (Case Reports in Cardiology)
Bradycardia and transient asystole are well-described sequelae of a myriad of neurologic insults, ranging from focal to generalized injuries. Increased vagal tone also predisposes many individuals, particularly adolescents, to transient neurally mediated bradyarrhythmia. However, prolonged periods of sinus arrest without junctional or ventricular escape are quite rare, even after significant neurologic injury. We describe the case of a 17-year-old man who presented with anoxic brain injury secondary to hemorrhagic shock from a stab wound to the neck. His recovery was complicated by prolonged periods of sinus arrest and asystole, lasting over 60 seconds per episode. This case illustrates that sustained asystolic episodes may occur following significant neurologic injury, and may continue to recur even months after an initial insult. Pacemaker implantation for such patients should be strongly considered.